Seven Tools as Quality Control to Reduce Defective Products in the Honeycomb Board Machine Process - Wiji Safitri; Ahmad Sutrimo; Miftakul Huda; Yoga Religia (DEAL: International Journal of Economics and Business, 2023)
Quality is a requirement for a product that will be distributed to consumers. Quality is also a competitive advantage for the company. PT NKR Industri as a company that produces paper still has not met the target to reduce the number of product defects. Product defects set by the company are a maximum of 3%, but currently product defects are up to 5%. Seven tools are tools used to control quality. This research is quantitative research. Data was collected through interviews and direct observation. The population and sample in this research is defect data on honeycomb board machines for the period July to December 2022. The data analysis technique uses seven tools. After mapping with seven tools, one of which is through a fishbone diagram, product defects that occur are caused by environmental factors consisting of room temperature, material factors consisting of damp paper and expired glue, method factors consisting of the dandori method is not suitable, machine factors consisting of less maintenance and the equipment has entered a maintenance period, the measurement factor consists of less carefull measurement process, and finally the man factor consists of lack of knowledge and not carefull.